The general theory on decision taking and it´s application in the medical assistance field (III) - Luis Alberto Corona Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
This article deepens on other aspects related to decision making, describing the relationships that are established between the types of problems and of decisions, as well as the qualities to make decisions effectively : experience,judge and creativeness and the relative importance of these qualities Other elements that affect decision making are also analyzed such as style of decision making and level of moral development. Emphasis is made on the ethical dimension.